2006
DOI: 10.1080/13691830600704149
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Conditions and the Healthy Immigrant Effect: Evidence from Canadian Immigrants

Abstract: The literature suggests that the foreign-born, and especially recent arrivals, enjoy better health than their Canadian-born counterparts, as measured by a number of health outcomes including self-assessed health and chronic conditions. Using data drawn from Statistics Canada's longitudinal National Population Health Survey (NPHS), the paper evaluates the so-called 'healthy immigrant effect' with respect to chronic conditions. Specifically, it evaluates the presence, number and type of chronic conditions (heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 26 publications
3
62
2
Order By: Relevance
“…Immigrants to Canada display better health outcomes than native-born Canadians (Beiser, 2005), and experience a lower number of chronic conditions than their native-born counterparts (Newbold, 2006;McDonald and Kennedy, 2004;Perez, 2002). This difference may due to Citizenship and Immigration Canada's (CIC) strict medical screening procedures on newcomers and/or its selection criteria (i.e., Federal Skilled Workers program) that favour younger individuals with advanced education and job skills (CIC, 2014).…”
Section: Immigration Acculturation and Health: The 'Healthy Immigranmentioning
confidence: 97%
“…Immigrants to Canada display better health outcomes than native-born Canadians (Beiser, 2005), and experience a lower number of chronic conditions than their native-born counterparts (Newbold, 2006;McDonald and Kennedy, 2004;Perez, 2002). This difference may due to Citizenship and Immigration Canada's (CIC) strict medical screening procedures on newcomers and/or its selection criteria (i.e., Federal Skilled Workers program) that favour younger individuals with advanced education and job skills (CIC, 2014).…”
Section: Immigration Acculturation and Health: The 'Healthy Immigranmentioning
confidence: 97%
“…Several explanations for this decline in health have been hypothesized, including poor access to the health care system, increased stress from migration and early settlement experiences, and acculturation (adoption of an unhealthy Canadian lifestyle). 2 The latter explanation includes the uptake of an unhealthy diet, which studies have acknowledged can be attributed to both individual (e.g., cultural food preferences, individual income) and environmental (e.g., food accessibility and availability) factors. [5][6][7] A growing body of research has focused on the role of diet in the health inequalities of immigrants.…”
mentioning
confidence: 99%
“…1 Recent evidence demonstrates that over time the health of immigrants declines with respect to chronic diseases, 2 self-reported health 3 and depression, 4 among others. Several explanations for this decline in health have been hypothesized, including poor access to the health care system, increased stress from migration and early settlement experiences, and acculturation (adoption of an unhealthy Canadian lifestyle).…”
mentioning
confidence: 99%
“…Although understanding the health trajectory is a foundation for effectively addressing how ethnic health disparities are shaped, current research has been limited when attempting to fully account for the complexity of the immigrant health trajectory, especially self-rated health, over time. 18,19,27 In Canada, the observations of the healthy immigrant effect and its decline phenomenon have been widely accepted in self-rated health 18,19,27,28 ; however, research on the self-rated health trajectory of immigrants has been far more limited, especially in findings from longitudinal studies and in the area of gender and ethnic health disparities. A few existing longitudinal studies from Germany and Australia have confirmed the healthy immigrant effect and its decline toward native-born levels within 5 years after arrival.…”
mentioning
confidence: 99%